Konjungsi Bi' dalam Teks Cerita Anak Bilingual: Analisis Sintaksis-Semantik - Hodairiyah, Hodairiyah; Arifah, Siti; Azis, Abdul; Wahedi, Salamet (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The study of syntax and semantics has direct relevance to the Madurese language so that a complete classification of both form and meaning can be carried out. Thus, this research is a qualitative descriptive study which aims to describe the distribution and meaning of the use of the bi' conjunction. The method used in providing data is the Simak method with basic tapping techniques and the advanced Simak, Bebas, Libat, Catat (SBLC) technique. Data obtained from the Bilingual Story Textbook (Madura-Indonesia). Researchers use syntactic and semantic theoretical approaches to analyze bi' conjunction data. Data analysis uses a collection method with Bagi Unsur Langsung (BUL) techniques with forwarding, replacement and loss techniques. The research results show that the characteristics of the bi' conjunction in Bilingual Children's story texts have a fixed position, have two or more conjunctions, and can be tied to conjunctions such as words, phrases and clauses. The meaning of the conjunction bi' also has a combination of pure, evaluative, implicative, paraphrastic and sequential meanings. Thus, this research still has the potential to be studied in more depth regarding the overall meaning of conjunctions with different objects.